The Effect of Tax Fairness, Tax Socialization and Tax Understanding on Tax Compliance: A Study on Micro, Small and Medium Enterprises (MSMEs) - Sizka Rismaningsih Lestary; Memed Sueb; Ivan Yudianto (Journal of Accounting Auditing and Business, 2021)
This research aims to identify the effect of fairness, socialization, and understanding on the Micro Small Medium Enterprises (MSMEs) taxpayer compliance towards Government Regulation number 23/2018 regarding income tax from business received or accrued by taxpayers who have certain gross turnover. This research used a quantitative approach, and data were collected using the Likert scale questionnaire. In this research, the population was 283 SME actors registered at the Cooperatives and Small and Medium Enterprises Office, Bandung. The sampling method used was purposive sampling. The data analysis technique used in this research is path analysis. Based on the partial test on the first regression model hypothesis, tax fairness and tax socialization are positively and significantly associated with the tax understanding. The second regression model hypothesis's partial test indicates that tax fairness does not affect, while the taxation socialization and understanding of taxation positively affect MSME taxpayers' compliance.